Effectiveness of Extracorporeal Shockwave Lithotripsy and Percutaneous Nephrolithotripsy for the Management of Moderate Size Kidney Stone - Tausif Ahmad, Khursheed Anwar, Noorshad Khan, Liaquat Ali Khan, Rafiullah (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To provide a specific guidance in managing renal stones. Study Design: Place and Duration of Study: Pakistan Atomic Energy Commission, General Hospital Islamabad from 1st 2018 to 30th November 2018. Methodology: Eighty two patients were included and divided into two groups. Patients in group A underwent ESWL, while those in group B underwent PCNL. All of the participants underwent thorough diagnostic and therapeutic procedures. As per inclusion and exclusion criteria, patients with renal stones (10-20 mm), detected by CT scan were selected for either ESWL or PCNL. Results: Thirty four patients in the PCNL group and 21 patients in the ESWL group, had post-operative hematuria at the time of presentation (p=0.072). There is a substantial difference between patients between 18-38 years and those in the 60+ years. According to the stone-free rate, 76 individuals had favourable results whereas only 6 had negative ones (p=0.756 and p=0.050). Conclusion: Extracorporeal shockwave lithotripsy and pecutaneous nepthrolithotripsy are both effective technique options for kidney stones. However, since ESWL is non-invasive and has fewer adverse effects than PCNL treatment option, it is more successful in treating medium-sized kidney stones (20 mm or smaller). Keywords: Extracorporeal shockwave lithotripsy, Percutaneous nephrolithotripsy, Kidney stone